2009
DOI: 10.1007/s00586-009-1012-y
|View full text |Cite
|
Sign up to set email alerts
|

Lumbosacral lordosis in fetal spine: genetic or mechanic parameter

Abstract: Many believe that the fetus spine had only one curvature from cranial to caudal which is a global kyphosis and that the lumbosacral lordosis appears with the erect posture. They agree that the sacrum of Homo sapiens is not positioned posteriorly at birth and that it is during the first few years that the sacrum, in humans, moves dorsally in relation with the progressive acquisition of erect posture and the ontogeny of bipedal locomotion. Nevertheless, there is no biometric study assessing these parameters in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
0
15
0
1
Order By: Relevance
“…Our youngest subjects were 2 years old and, by that age, most children have already begun to walk and vertically load their spines. The presence of lordosis at the L5-S1 segment during in utero development has been reported in one study (Choufani et al, 2009). The PI of neonates (27.2 AE 12.8) is less pronounced than that of children who are old enough to walk unassisted (Table 3).…”
Section: Discussionmentioning
confidence: 70%
“…Our youngest subjects were 2 years old and, by that age, most children have already begun to walk and vertically load their spines. The presence of lordosis at the L5-S1 segment during in utero development has been reported in one study (Choufani et al, 2009). The PI of neonates (27.2 AE 12.8) is less pronounced than that of children who are old enough to walk unassisted (Table 3).…”
Section: Discussionmentioning
confidence: 70%
“…In contrast, a longitudinal study of 11 to 22‐year‐olds found no relationship between BMI and the development of thoracic kyphosis (16). Sagittal spinal posture development may be influenced by genetics (17), gender (16,18–22), exercise levels (23), height (14), school furniture (24) and generation (25).…”
Section: Introductionmentioning
confidence: 99%
“…The human body, including the spinal curvatures, changes during ontogeny and phylogeny [1,2], which is reflected by the instability of characteristics and indicators of body build and posture. The period of ontogenetic stabilization between 20 and 40 years of age, accompanied by the inhibition of growth processes and establishment of body proportions does not guarantee discontinuation of the variability of physiological spinal curvatures.…”
Section: Introductionmentioning
confidence: 99%